Development of a Learning Management System Using Google Sites in Chemistry Lessons - Zulkifli Zulkifli; Faiza Rini; Dina Ramadhanti (Journal of Computer-based Instructional Media, 2025)
Low student learning outcomes in Chemistry at SMAN 1 V Koto Kampung Dalam, Padang Pariaman Regency, are caused by teachers' limitations in utilizing interactive digital learning media. Learning is still dominated by conventional methods, while students need attractive visual and digital media to understand abstract Chemistry concepts. This study aims to develop and test the validity, practicality, and effectiveness of a Google Sites-based Learning Management System in Chemistry learning. The method used is Research and Development (R&D) with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 30 grade XI students selected through random sampling from a total population of 92 students. The research instruments included an expert validation sheet, a teacher and student practicality questionnaire, and a learning outcome test (pre-test–post-test). The results showed that the Google Sites-based learning management system was rated "Highly Valid" by subject matter and media experts and "Highly Practical" according to teacher and student responses. The effectiveness test using the Wilcoxon Signed-Rank Test produced a significant value of 0.000 (<0.05) and an N-Gain score of 0.83 in the "Effective" category. Future work is recommended to integrate this learning management system with learning analytics and mobile learning features to expand its effectiveness in sustainable digital learning.